Transformasi Bahasa Formal ke Dalam Bahasa Adat Menggunakan Makna Budaya (STUDI KASUS MASYARAKAT ADAT KASEPUHAN – CIPTAGELAR DAN TAMAN NASIONAL GUNUNG HALIMUN) - Andri Hernandi (Fakultas Seni Rupa dan Desain ITB, 2006)
The shared thinking pattern between the information provider and the information recipient is the key to the success of their communication. Therefore, both the information provider and recipient have to use the same language, or the language that has been converted into the recipient’s language. In the case of the communication between the Cipta Gelar community and the Halimun Mountain Park’s Officers (the information provider), the officers have to convert their formal language into the language of Cipta Gelar community’s local language. Without such an effort, a conflict of interest between the two parties may arise as to who deserves to have the authority to manage the forestry and other potential natural resources of Halimun and Salak Mountain range. Overall, whoever has the authority to manage the range of the two mountains, the problem will be about the effectiveness of communication, which is mainly caused by the language difference – not by the management authority itself. The communication problem between the Halimun Mountain Park’s Officers and the Cipta Gelar community is because of the fact that the officers use the formal language whose basis is the positive laws while the Cipta Gelar local community uses the language whose basis is the karma laws, which have some bearing on spiritual culture and mysticism. In order that the Cipta Gelar local community understands the language of the Halimun National Mount Park officers, the park management party uses the language into which the cultural meanings of the Cipta Gelar local people are integrated. In conclusion, to understand a local language of a local people, one has to understand the local people’s spiritual culture, which is sometimes irrational and tends to encompass the rational religious intuition zone, has to be taken into account.